Review Sistematik: Model Pemulihan Penderita Gangguan Jiwa Berat Berbasis Komunitas - Retno Lestari; Ah Yusuf; Rachmat Hargono; Febri Endra Budi Setyawan (Puslitbang Sinergis Asa Professional, 2020)
People with severe mental illness have complex disabilities affecting mental functions, daily activities, and social life, thus they need help from others in carrying out daily functional activities. Optimizing the recovery of severe mental illness requires a holistic approach and integration between mental health services and supportive communities so that sufferers can interact with others, have a positive self-concept, and improve their well-being. This study aims to describe a community-based model of recovery for people with severe mental illness. Several literature studies were obtained from 50 reference sources through Science Direct, Google Scholar, Proquest Health and Medical Complete, Proquest Nursing, and Allied Health Sources from 2009 to 2019. Results explain that the community provides an adequate support system in improving the care of people with severe mental illness. Support systems in the community involve social and physical aspects as well as the economic infrastructure through employment opportunities or financial support and a decent living. The interaction between community members and people with severe mental illness could be a positive thing in strengthening the motivation of people with severe mental illness to recover and be able to do their activities independently. The recovery process of severe mental illness requires strong motivation and commitment from the sufferer, the family, all society members, community mental health service team, and related policymakers. It can be concluded that people with severe mental illness need support from various parties in terms of future life planning, identifying strengths and weaknesses that they have, and recognizing multiple obstacles and support so that they recover and live independently.